Desain Dan Pembuatan Inovatif Peralatan Pengasapan Ikan (Salai) Ramah Lingkungan Untuk Mendapatkan Suhu Dan Waktu Yang Optimal - Safentry, Aan; Rochyani, Neny; Nurlela, Nurlela; Wahyudi, Agus (Universitas PGRI Palembang, 2025)
This study aims to design and make an environmentally friendly fish smoking tool and contribute to the improvement of fish smoking practices and the utilization of coconut shell waste with a focus on determining the optimal temperature and time for smoking catfish using coconut shell waste as fuel and smoking tools using drum smoker type. The research method includes experiments (experiments) to reduce the mass of samples with time variations (4 hours, 5 hours, 6 hours), temperature variations (90 ° C, 100 ° C, 110 ° C) and organoleptic tests (appearance, taste, texture, and odor). From the results of the study, it was obtained that the optimal temperature and time for smoking salai patin fish had been carried out 3 times the experiment of smoking patin fish with temperatures of 90 ° C, 100 ° C, and 110 ° C respectively with variable times of 4, 5, and 6 hours, the ideal temperature was obtained for the process of smoking salai patin fish using this tool at a temperature of 100 ° C within 5 hours this was analyzed in terms of the appearance of color, taste, texture and smell of salai patin fish.